The economics of patient safety Part IV: Safety in the workplace Occupational safety as the bedrock of resilient health systems - de Bienassis, Katherine (OECD Health Working Papers, 2021)
Health care settings are inherently hazardous places, with very unpredictable and complex working environments. These hazards and risks not only result in a range of injuries and ill-health among workers but also jeopardise the safety of patients. The COVID-19 crisis has amplified the importance of ensuring that the health care that is provided is safe-for patients and health workers alike. A sufficient, and capable, workforce, is the foundation of resilient systems. Policy makers need to focus now on how to build and support an appropriate workforce to respond to future shocks. This includes health workers beyond the hospital-including those in community, long-term, and primary care. The safety of both patients and health workers should be protected through appropriate mechanisms to ensure the safety of protective equipment and sufficient supplies, appropriate staffing levels, training and support at the workplace. These governance mechanisms are even more relevant when policy makers face trade-offs between health, safety and economic concerns